Case Report: Combined Autoimmune Pancreatitis, Ulcerative Colitis and Sclerosing Cholangitis in 28-y.o. Patient - A. R. Khurmatullina; A. V. Okhlobystin; L. N. Androsova; R. T. Rzayev; A. S. Tertychnyy; A. P. Kiryukhin; O. Z. Okhlobystina; M. S. Zharkova; O. S. Shifrin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to demonstrate difficulties of differential diagnostics in the case of combined autoimmune pancreatitis, sclerosing cholangitis and ulcerative colitis. Colonic lesions that initially had low grade of inflammation were resistant to immunosuppressive therapy.Key points. A 28-year-old female patient was admitted to the clinic for jaundice associated with pruritis. Based on the characteristic beaded appearance of the intrahepatic bile ducts at magnetic resonance cholangiopancreatography, primary sclerosing cholangitis (PSC) was diagnosed. Subsequent examination revealed focal pancreatitis and total colitis with histological pattern, consistent with ulcerative colitis (UC). To determine the etiology of pancreatitis IgG4 serum level was examined, that showed over 2-fold elevation. This required differential diagnostics between PSC with IgG4 elevation, UC and type 2 autoimmune pancreatitis (AIP) (more common in European population) on one hand and IgG4-associated systemic disease (more common in Asian population) with bile ducts, pancreas and large intestine involvement on the other. Liver histology failed to reveal histological signs characteristic of any type of cholangitis, pancreatic biopsy was not performed. Immunosuppressive therapy (steroids followed by thiopurines) resulted in rapid improvement of the pancreatic changes while no response was achieved for bile ducts and the colon that was in favor of the first concept (PSC + type 2 AIP + UC). The patient was recommended to receive biologic therapy for UC remission induction.Conclusion. Differential diagnostics of combined autoimmune lesions of the liver, the pancreas and colon may be complicated and carried out ex juvantibus according to response to immunosuppressive therapy.